ASSOCIATION OF POSITIVE MENTAL HEALTH LITERACY WITH MENTAL WELL-BEING AMONG UNDERGRADUATE STUDENTS OF NAZARBAYEV UNIVERSITY - Akisheva, Guldana (Nazarbayev University School of Medicine, 2022)
Background The increase in the prevalence of mental disorders in young adults requires more attention on improving mental health and mental health literacy (MHL). Although majority of previous studies focused on recognition and prevention of mental illnesses, very few studies were focused on positive mental health literacy (PMeHL), part of MHL which defines knowledge about how to obtain and maintain good mental health. Therefore, the aim of this study was to examine the relationship between positive mental health literacy and mental well-being of undergraduate students in Kazakhstan. Methods The data was obtained from a cross-sectional study based on a survey of 122 undergraduate students aged 18–22 years at Nazarbayev University in Nur-Sultan city. WHO-5 Well-Being Index was utilized to evaluate mental well-being, and Mental Health Promoting Knowledge-10 item scale (MHPK-10) was used to assess PMeHL. The relationship was evaluated using a multiple linear regression model adjusting for possible covariates, including socio-demographic and lifestyle characteristics of students. Statistical threshold was determined at p<0.05. Results The sample included 35% of males and 65% of females, with the mean age of 19.5 years. PMeHL had a positive impact on mental wellbeing, where every increase in the score of PMeHL was significantly associated with increase in the score of mental well-being by 0.23, while adjusting for gender, age, family’s support, father’s education level, and physical exercising behaviour. Additionally, gender differences were observed in mental well-being, where mean of mental well-being was equal to 2.80 for males and 2.27 for females. Gender, physical exercising behaviour, father’s degree of education, family’s support were found to be sufficient in predicting mental wellbeing of undergraduate students. Conclusion Current study determined the positive impact of PMeHL on undergraduate students’ well-being. Additionally, family’s support and physical exercising behaviour have shown an advantageous effect on establishing better mental wellness. The results of the study can be used by stakeholders of Kazakhstan in public health campaigns that are focused on the improvement of adolescents’ mental health. Keywords: mental well-being, positive mental health literacy, undergraduate students, Kazakhstan, survey
Keywords: Health Literacy; Multiple Linear Regression; Mental Health Literacy; Type of access: Gated Access; mental well-being; positive mental health literacy; undergraduate students; Kazakhstan; survey